Potency of Cinnamomum burmannii as Antioxidant and α Glucosidase Inhibitor and Their Relation to Trans-Cinamaldehyde and Coumarin Contents - Djadjat Tisnadjaja; Herman Irawan; Nurlaili Ekawati; Bustanussalam Bustanussalam; Partomuan Simanjuntak (Jurnal Fitofarmaka Indonesia, 2020)
Cinnamon (Cinnamomum spp) is one of important export commodity for Indonesia. With annual production capacity about 103.594 tons, Indonesia is one of main cinnamon’s exporter especially to United States. Recently the utilization of cinnamon is developed, where not only use as spices but also use in pharmaceutical and cosmetic industries. The development of cinnamon’s use of course might lead to the market growth.. But on the other side arise an issue about coumarin content, where Cinnamomum burmannii issued to have higher content of this hepatotoxic compound than Cinnamomum verum or Cinnamomum zeylanicum. This research result showed that, although coumarin content of Indonesian Cinnamomum burmannii is higher than Cinnamomum zeylanicum but the difference is not too significant. C. burmannii collected from Gunung. Mas, West Java has coumarin content of 0.0030 % which is slightly higher than C. zeylanicum (0.0017 %). This research result also shown that antioxidant activity and α glucosidase inhibition activity is related to polyphenol and flavonoid content.